Islamic Education Students’ Perceptions of AI in Learning Islamic History - Boangmanalu, Adi Zulkifli; Dahlan, Zaini (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores Islamic Religious Education (PAI) students’ perceptions of Artificial Intelligence (AI) in learning Islamic Education History, prompted by AI’s growing adoption for academic tasks like writing, discussions, and summarization. Using a qualitative case study approach, data were collected via in-depth interviews and observations of 2024 cohort PAI students at FITK, State Islamic University of North Sumatra. Findings indicate positive views of AI as a tool to streamline tasks and simplify material comprehension, though dependency emerged during time constraints or difficulty understanding sources. While cognitively beneficial, AI was perceived as inadequate for conveying the depth of Islamic historical and spiritual values. Students emphasized the need for lecturer guidance and institutional policies to ensure ethical, responsible use. The study concludes that AI is a valuable yet incomplete tool, requiring balance with comprehension and academic ethics to uphold Islamic education’s essence.